Development of a barcode-based inventory system for AMT laboratory tools at PhilSCA, Philippines - Danielle Jane Elec; Mark Louie Martin; Maria Jessica Martin (Diversitas Journal)
This study was conducted to evaluate the effectiveness of barcode system for tool monitoring and inventory management in a laboratory environment; to improve productivity among students, teaching staff, and non-teaching staff while promoting a sense of responsibility. The developed and tested barcode system saved time, minimized errors, and enhanced technological learning in tool transactions. The 80 participants involved in this study were from the AMT program at Philippine State College of Aeronautics, including 1st and 2nd year students, faculty instructors, and AMT tool keeper. Mixed-method approach was employed. Demonstration of barcode system initiated the participants to evaluate and provide feedback regarding its usage and benefits, which was assessed using Likert scale. Statistical treatments (frequency and percentage distribution, weighted mean, and independent sample t-test) were utilized for analysis. The barcode system surpassed participants' expectations, and met requirements for tool monitoring and inventory. Participants strongly agreed on the system being accurate, technologically advanced, and cost-effective. Implementing the system can enhance borrower tool keeper accountability,  and improve transaction convenience and efficiency. These findings suggest that replacement of manual process with barcode system is highly recommended despite the need to improve security measures. The results could be used in proposing improvements and effective implementation for the current tool monitoring system in the AMT laboratory. Overall, this research showed benefits of implementing barcode system for the students, teaching, and non-teaching staff. Implementing barcode system would allow the institution to equip students with knowledge and experience through advanced technology aligned with the practices in aviation industry.